2011
DOI: 10.1016/j.jlumin.2010.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Assignments and optical properties of X-ray-induced colour centres in blue and orange radiophotoluminescent silver-activated glasses

Abstract: We have systematically investigated the origin and optical properties of the X-ray-induced colour centres based on the blue and red radiophotoluminescence (RPL) in a silver-activated phosphate glass. The induced-absorption band was decomposed into six Gaussian bands on the basis of its strong analogy with silver-activated sodium chloride. We have ascribed these bands to Ag 0 , Ag 2+ , Ag 2 + and other silver ion species by means of optical and thermal measurements such as colour centre formation and dissolusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(28 citation statements)
references
References 26 publications
(34 reference statements)
4
24
0
Order By: Relevance
“…In addition, the origin, formation kinetics and optical properties of X-ray-induced Ag centres were also investigated through various methods [15,16].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the origin, formation kinetics and optical properties of X-ray-induced Ag centres were also investigated through various methods [15,16].…”
Section: Resultsmentioning
confidence: 99%
“…To correct the over-response in the low-energy range, Manninen et al [23] reported that a filter composed of tin (Sn) is useful for energy compensation in the diagnostic energy range (50-125 keV), while the filter is not required in the radiation therapy energy range (6)(7)(8)(9)(10)(11)(12)(13)(14)(15) MeV) when using commercially available GD-352M and GD-302M (Asahi Techno Glass Corporation) type glasses based on the RPL phenomena.…”
mentioning
confidence: 99%
“…Recently, we have systematically investigated the assignments and optical properties of X-ray-induced silver-related species of PG:Ag by means of various optical measurements such as RPL decay curve analysis, peak fitting analysis and heat treatments (Kurobori et al, 2010;Zheng and Kurobori, 2011). It was established from these results that the decomposed six Gaussian bands induced by X-ray irradiation in PG:Ag were, in turn, attributed to Ag + , Ag 3 + or Ag 3 2+ , Ag 2 + , Ag 2+ , Ag 0 and hole-trap centres, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the origin, formation kinetics and optical properties were also investigated with a peak-fitting analysis, a high-repetition-rate femtosecond (fs) laser technique, an RPL decay curve analysis, a heat treatment, and transmission electron microscopy (TEM) (Zheng and Kurobori, 2011a;Zheng et al, 2011;Zheng and Kurobori, 2011b).…”
Section: Resultsmentioning
confidence: 99%